Effect of tualang honey supplementation in weight reduction and dyslipidemia in high cholesterol diet induced obese rats - Abu Hanifah, Nabihah; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Abdullah, Nor Zamzila; Buyong, Zunariah; Ahmad Affandi, Khairunisa; Abdul Rahim, Roslina; Ahmad, Hajar Fauzan (Faculty of Medicine, UKM, 2024)
Introduction: Obesity is a key risk factor for many chronic diseases. Malaysia records the highest prevalence of obesity in Southeast Asia. Tualang honey has been proven to treat other chronic diseases but its effect on weight reduction is not well-studied. This study aimed to investigate the effect of Tualang honey (TH) supplementation on body weight and lipid profile in 12% high cholesterol diet (HCD) induced obesity rat model. Materials and method: Forty male Sprague-Dawley rats were divided into 5 groups with their respective diet for 12 weeks followed by respective treatment for the following 6 weeks. The groups are: Group 1 (normal diet), Group 2 (normal diet and TH 3.0g/kg), Group 3 (12% HCD), Group 4 (12% HCD and TH 3.0 g/kg), and Group 5 (12% HCD and Orlistat 10 mg/kg). Their body weight was measured weekly. At the end of the study, blood was collected for lipid profile via retro-orbital bleeding. Results: We demonstrated a significantly lower final body weight of rats in Group 2 (328.25 + 25.49 g) compared to Group 1 (409.13 + 16.33 g) (p<0.001) and in Group 4 as compared to Group 3 (343.88 + 44.24 g vs 471.00 + 19.55 g, p<0.001). There is no significant difference in final body weight between Group 4 and Group 5 (343.88 + 44.24 g vs 354.25 + 32.27 g, p>0.05). The administration of TH also significantly reduces the cholesterol level in Group 4 compared to Group 3 (Med= 1.83 mmol/L, IQR= 0.68 vs Med=3.20 mmol/L, IQR= 0.80, p<0.05). The lowest concentration of triglycerides was recorded in Group 4 with a significant difference when compared to Group 3 (Med= 0.85 mmol/L, IQR= 0.28 vs Med= 1.45 mmol/L, IQR= 0.95, p=0.001). Conclusion: Tualang honey supplementation has been shown to reduce body weight, total cholesterol, and triglyceride levels in 12% of HCD-induced obese rats.